(untitled) (Asia Pacific Journal of Social Innovation, 2024)
We studied the alpha (OC) and functional (trophic) diversity of fishes that thrive in a seagrass bed in Pitogo, Zamboanga City. Replicate fish samples were collected using a 20-m long gill net set for 30 min. The Shannon diversity index for fishes identified up to the Genus level) was comparable within the hahital. Fish stomach contents were analyzed following the numerical method. The Shannon diversity indices for the dietary items indicate that Choerodon and Pseudobalistes are highly carnivorous, the Rhinecanthus is herbivorous and the rest of the genera (Apogon, Balistes, Chaetodon, Cheilinus, Gerres, Halichoeres, Lethrinus, Lutjanus, Rypticus and Scarus) are omnivorous. Overlap in diet is apparent among these genera, but partitioning is achieved by differences in the relative intensity of consumption of certain dietary items.